Lighting the Patient Room of the Future: Evaluating Different Lighting Conditions From the Patient Perspective. (April 2022) - DuBose, Jennifer; Davis, Robert G.; Campiglia, Gabrielle; Wilkerson, Andrea; Zimring, Craig
Objective: This study explores whether "future" lighting systems that provide greater control and opportunity for circadian synchronization are acceptable to participants in the role of patients. Background: Tunable, dimmable light emitting diode systems provide multiple potential benefits for healthcare. They can provide significant energy savings, support circadian synchronization by varying the spectrum and intensity of light over the course of the day, address nighttime navigation needs, and provide user-friendly control. There is an emerging understanding of the important visual and nonvisual effects of light; however, important questions remain about the experience and acceptability of this "future" lighting if we are to adopt it broadly. Methods: Volunteer participants (34) performed a series of tasks typical of patients, such as reading or watching a video, in a full-scale simulated inpatient room. Each participant conducted these tasks under 12 lighting conditions in a counterbalanced order that included varying illuminance levels, correlated color temperatures (CCTs), and in a few conditions, saturated colors. The participants rated each lighting condition on comfort, intensity, appropriateness, and naturalness. Results and Conclusions: The participants found that conditions with CCTs of 5, 000 K and higher were significantly less comfortable and less natural than conditions with lower CCTs. Conditions with lighting distributed in multiple zones in the patient room were viewed more favorably than a traditional overbed configuration. The participants in this simulated patient study reacted negatively to colored lighting on the footwall of the room but found a mixture of warmer and cooler luminaire CCTs acceptable.